STUDI TERHADAP PESERTA DIDIK YANG MENGALAMI KEJENUHAN DALAM MENGIKUTI PEMBELAJARAN DARING - Ester Novialistra; Indri Astuti; Purwanti Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the study of students who experience boredom in participating in online learning for class X State Senior High School 1 Meranti. the sample in this study was class X students totaling 3 students, the sample was taken based on the needs in the study, namely students who experienced boredom when learning online, the research method used was descriptive in the form of a qualitative approach while data collection techniques used interview and documentation techniques, Activities in data analysis, namely, data reduction, data presentation, and conclusions or verification. The results show the characteristics of students who experience boredom in online learning: 1) the JAA subject has the characteristics that appear to him, namely lethargy, and not enthusiastic, 2) the FA subject has visible characteristics, namely procrastinating on doing assignments, 3) the NSL subject has characteristics that It seems that you often feel bored. Factors causing saturation: 1) JAA subjects are family factors, school environment, community environment, 2) FA Subjects are physiological factors, family factors, school environmental factors, 3) NSL subjects are physiological factors, school environmental factors, community environmental factors. The impact of boredom: 1) JAA subjects decreased academic achievement, lost motivation to learn, lacked interaction, 2) FA subjects decreased academic achievement, lost motivation to learn, lacked interaction, 3) NSL subjects lacked interaction with teachers and friends